2023
DOI: 10.1038/s41586-023-06840-9
|View full text |Cite
|
Sign up to set email alerts
|

A synthesis of evidence for policy from behavioural science during COVID-19

Kai Ruggeri,
Friederike Stock,
S. Alexander Haslam
et al.

Abstract: Scientific evidence regularly guides policy decisions1, with behavioural science increasingly part of this process2. In April 2020, an influential paper3 proposed 19 policy recommendations (‘claims’) detailing how evidence from behavioural science could contribute to efforts to reduce impacts and end the COVID-19 pandemic. Here we assess 747 pandemic-related research articles that empirically investigated those claims. We report the scale of evidence and whether evidence supports them to indicate applicability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 133 publications
0
3
0
Order By: Relevance
“…Furthermore, the experience of social relationships changed during the COVID-19 pandemic with individuals turning to more remote methods of communication (Ofcom, 2020). From a policy perspective, it will be important to critically investigate the effectiveness of online tools, such as social media, to buffer against negative mental health effects in vulnerable young people (Orben et al, 2020;Ruggeri et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the experience of social relationships changed during the COVID-19 pandemic with individuals turning to more remote methods of communication (Ofcom, 2020). From a policy perspective, it will be important to critically investigate the effectiveness of online tools, such as social media, to buffer against negative mental health effects in vulnerable young people (Orben et al, 2020;Ruggeri et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…21 22 Despite unprecedented levels of vaccine access and nearly real time communication on the development and availability of vaccines in 2020-21, public health officials struggled to keep pace with misleading or inaccurate content online. 23 As guidelines shifted with the emergence of new information, policy decisions were often perceived by individuals and groups who are prone to distrust or refute government messaging as a response not to evidence but to mistakes or lack of expertise. 24 25 A 2021 randomised controlled trial (RCT) found that exposure to misinformation about covid-19 vaccines lowered the intent of recipients to vaccinate, even among those reporting before exposure that they would "definitely" accept vaccination.…”
Section: Behavioural Interventions To Reduce Vaccine Hesitancy Driven...mentioning
confidence: 99%
“…The first three articles of this special issue relate to a notable theme that emerged during IBPPC 2022the application of BPP during the COVID-19 pandemic. The pandemic underscored the significance of behavioural science and public policy for exploring effective strategies in public health (Ruggeri et al, 2024). Before vaccines were widely available, behaviour change interventions were among the only approaches to curb infection rates.…”
Section: About This Special Issuementioning
confidence: 99%